(untitled) (Research, Society and Development, 2022)
The objective was to improvethe experience experienced by nursing students in practice of the curricular component "Child and Adolescent Health in Primary Care". The methodology was a descriptive study of qualitative approach, of the type of experience report. The study participants were composed of 10 parents of children in the early childhood age group, who attended the nursing consultation in childcare. Bardin’s proposed content analysis technique was used to analyze and interpret the collected data. The results were obtid during childcare consultations performed, parents were asked about the use of PICs in children, and they reported that they used lemon balm tea for cramps, abdominal massages for constipation and the use of music to calm the baby. Based on this, the discussion was made to guide issues of the theme, and the hypothesis of the functionality of integrative and non-pharmacological practices in early childhood children was raised. It is concluded that PICs appear as a non-drug form for the relief of common symptoms in early childhood. Thus, nursing plays a prominent role in guiding the proper use of these practices, with the purpose of ensuring holistic, qualified and humanized care to the user. Thus, it is noted the relevance of training and continuous updating of the professional in the face of PICS. Nevertheless, it is important to highlight the lack of articles with the same scientific bias, which demonstrates the need for scientific productions that can explain and report on the applicability of PICs in children.